Peculiarities of Interconnection of Labour Motivation and Organizational Culture in Commercial Banks in Altai Region - ДолженкоРуслан Алексеевич (Journal of Economic Sociology, 2010)
The paper is devoted to the interconnection of labour motivation system and organizational culture in commercial banks. The research covers several banks of Barnaul city in Altai region. The main issues discussed in the paper follow as: in which way can system of labour motivation and organizational culture be interconnected? How can the impact of values of a specific type of organizational culture be taken into account while a given bank’s system of labour motivation is being formed?